The effect of Extreme Low Frequency-Pulsed Electromagnetic Field exposure in the healing process of Sprague Dawley mouse delayed union femur fracture: study of Rust Radiology Score - djaja, andika (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
Fractures usually heal normally. In some conditions, the healing process do not occur normally, but become delayed union or non union as a complication. Successful healing of fractures is a complex interaction between the process of angiogenesis and osteogenesis (the interaction of osteoblasts and osteoclast). Physical stimuli such as exposure of EMF (electromagnetic fields) influences of the osteogenesis process both in the development stage of embryo reinforcement and the fracture healing stage. The aim of this study is to determine the healing of delayed union fractures in experimental animals due to the expossure of Extreme Low Frequency-Pulsed Electromagnetic Field (ELF-EMF) by comparing the RUST scores. The experimental study was conducted Department of Nutrition Animal Laboratory, Faculty of Medicine, Universitas Indonesia with 56 experimental rats during August-September 2018. There were no differences of animal characteristics in the study. It was found that there were significant differences in Rust Score in the treatment and control groups in each examination week. There were no differences in clinical improvement in the two groups. This study concluded that there was an improvement in delayed union fracture healing after the administration of ELF-EMF as seen from the difference in Rust score.